Abruptio placentae in cynomolgus macaques (Macaca fascicularis): male bias. Issue 4 (27th April 2013) - Schlabritz‐Loutsevitch, N.; Schenone, A.; Schenone, M.; Gupta, S.; Hubbard, G.; Zhang, J.; Mari, G.; Dick, E.
Abstract Background Abruptio placentae is a serious problem with a high rate of maternal and fetal mortality and documented sexual dimorphism in reoccurrence. Macaca fascicularis is a well‐described reproductive model; however, there are no data available regarding sexual dimorphism in abruptio placentae in these species. Methods A retrospective study of pathology and medical records in a large colony of M. fascicularis was performed. Placental specimens were analyzed. Results The incidence of placenta abruptio in the colony was 15.7/1000 births. In the abruptio placentae group, male fetuses had lower placental disk length and increased femur length compared with female fetuses. The feto‐pacental ratio and fetal weight were lower in the male fetuses in the abruption group compared with those in the stillbirth group without abruption placentae. Conclusion This is the first documentation of male bias in placental and fetal development in abruptio placentae in non‐human primates.